Augmentation Therapy with Alpha-1 Antitrypsin: Present and Future of Production, Formulation, and Delivery - Bianchera, Annalisa; Alomari, Esraa; Bruno, Stefano (Current Medicinal Chemistry, 2022)
Alpha 1-antitrypsin is one of the first protein therapeutics introduced on the market more than 30 years ago, and to date, it is indicated only for the treatment of the severe forms of a genetic condition known as alpha-1 antitrypsin deficiency. The only approved preparations are derived from plasma, posing potential problems associated with its limited supply and high processing costs. Moreover, augmentation therapy with alpha-1 antitrypsin is still limited to intravenous infusions, a cumbersome regimen for patients. Here, we review the recent literature on its possible future developments, focusing on i) the recombinant alternatives to the plasma-derived protein, ii) novel formulations, and iii) novel administration routes. Regulatory issues and the still unclear noncanonical functions of alpha-1 antitrypsin, possibly associated with the glycosylation pattern found only in the plasma-derived protein, have hindered the introduction of new products. However, potentially new therapeutic indications other than the treatment of alpha-1 antitrypsin deficiency might open the way to new sources and new formulations.
Keywords: augmentation therapy